3D microperfusion of mesoscale human microphysiological liver models improves functionality and recapitulates hepatic zonation - Wesseler, Milan Finn; Taebnia, Nayere; Harrison, Sean; Youhanna, Sonia; Preiss, Lena C; Kemas, Aurino M; Vegvari, Akos; Mokry, Jaroslav; Sullivan, Gareth J; Lauschke, Volker M; Larsen, Niels B (Acta biomaterialia, 2023)
Hepatic in vitro models that accurately replicate phenotypes and functionality of the human liver are needed for applications in toxicology, pharmacology and biomedicine. Notably, it has become clear that liver function can only be sustained in 3D culture systems at physiologically relevant cell densities. Additionally, drug metabolism and drug-induced cellular toxicity often follow distinct spatial micropatterns of the metabolic zones in the liver acinus, calling for models that capture this zonation. We demonstrate the manufacture of accurate liver microphysiological systems (MPS) via engineering of 3D stereolithography printed hydrogel chips with arrays of diffusion open synthetic vasculature channels at spacings approaching in vivo capillary distances. Chip designs are compatible with seeding of cell suspensions or preformed liver cell spheroids. Importantly, primary human hepatocytes (PHH) and hiPSC-derived hepatocyte-like cells remain viable, exhibit improved molecular phenotypes compared to isogenic monolayer and static spheroid cultures and form interconnected tissue structures over the course of multiple weeks in perfused culture. 3D optical oxygen mapping of embedded sensor beads shows that the liver MPS recapitulates oxygen gradients found in the acini, which translates into zone-specific acet-ami-no-phen toxicity patterns. Zonation, here naturally generated by high cell densities and associated oxygen and nutrient utilization along the flow path, is also documented by spatial proteomics showing increased concentration of periportal- versus perivenous-associated proteins at the inlet region and vice versa at the outlet region. The presented microperfused liver MPS provides a promising platform for the mesoscale culture of human liver cells at phenotypically relevant densities and oxygen exposures. STATEMENT OF SIGNIFICANCE: A full 3D tissue culture platform is presented, enabled by massively parallel arrays of high-resolution 3D printed microperfusion hydrogel channels that functionally mimics tissue vasculature. The platform supports long-term culture of liver models with dimensions of several millimeters at physiologically relevant cell densities, which is difficult to achieve with other methods. Human liver models are generated from seeded primary human hepatocytes (PHHs) cultured for two weeks, and from seeded spheroids of hiPSC-derived human liver-like cells cultured for two months. Both model types show improved functionality over state-of-the-art 3D spheroid suspensions cultured in parallel. The platform can generate physiologically relevant oxygen gradients driven by consumption rather than supply, which was validated by visualization of embedded oxygen-sensitive microbeads, which is exploited to demonstrate zonation-specific toxicity in PHH liver models.
Keywords: hepatocyty; Hydrogels; Hepatocytes; Oxygen; Liver; kyslík; lidé; játra; Humans; hydrogely